The Nazeris fauna of the Leigong Mountain, Guizhou, China (Coleoptera, Staphylinidae, Paederinae) - Lin, Xiao-Bin; Yu, De-Hui; Hu, Jia-Yao (Zootaxa, 2022)
Seven species of Nazeris Fauvel, 1873 are reported for Guizhou, China. All of them are described as new: N. ingentis Lin, Yu & Hu, sp. n., N. resimus Lin, Yu & Hu, sp. n., N. leigongensis Lin, Yu & Hu, sp. n., N. yujiei Lin, Yu & Hu, sp. n., N. muricatus Lin, Yu & Hu, sp. n., N. excertus Lin, Yu & Hu, sp. n. and N. serratus Lin, Yu & Hu, sp. n.